Observer-based reliable control for switched systems with immeasurable states by the parallel triggering mechanism - Zhao, Jianrong; Liu, Wei; Lu, Junwei; Zhang, Dan (IET control theory & applications, 2020)
This study is concerned with the observer-based reliable control problem for switched systems subject to actuator faults via the parallel triggering mechanism. Exponential observers and error systems are constructed due to the immeasurable system state. Since system modes and sampling controller modes may be mismatched, no more than one switching and multiple switchings are both considered in one triggering dependent sampling interval. Combining the mode-dependent average dwell time technique with the parallel triggering mechanism, sampling controllers are designed to realise the reliable control for switched systems subject to actuator faults. By this mechanism, decay rates of observer states are added into triggering conditions; the execution number of control tasks is reduced with similar system performances in the meantime. At last, the effectiveness of proposed results is illustrated by a simulation example.